Prevalence and patterns of cigarette smoking before and during early and late pregnancy according to maternal characteristics: the first national data based on the 2003 birth certificate revision, United States, 2016 - Anthony J. Kondracki (Reproductive Health, 2019)
Abstract Background The objective of this study was to examine the prevalence of smoking by intensity status before pregnancy and during early (first and second trimester) and late (third trimester) pregnancy according to race/ethnicity, age, and educational attainment of women who gave birth in the United States in 2016. Methods This cross-sectional study was based on the 2016 National Center for Health Statistics (NCHS) Natality File of 3,956,112 live births, the first year that it became 100% nationally representative. Self-reported smoking data were used to create new seven smoking intensity status categories to capture natural variability in smoking patterns during pregnancy and to identify maternal smokers by race/ethnicity, age, and educational attainment. The risk of smoking at low and high intensity in early pregnancy was estimated in multivariable logistic regression analyses. Results Nearly 9.4% of women reported smoking before pregnancy and 7.1% during pregnancy, both at high and low intensity, and smoking rates were higher in the first trimester (7.1%) than in the second (6.1%) or the third (5.7%) trimester. Non-Hispanic White women, women 20–24 years old, and women with less than a high school education were the strongest predictors of smoking anytime during pregnancy. The odds of smoking in early pregnancy at high intensity were 88% lower (aOR 0.12, 95% CI: 0.11, 0.13) for Hispanic women, compared to non-Hispanic White women; 16% higher (aOR 1.16, 95% CI: 1.12, 1.21) for women 20–24 years old and 16% lower (aOR 0.84, 95% CI: 0.80, 0.89) for women ≥35 years old, compared to women 25–29 years old; as well as 13% higher (aOR 1.13, 95% CI: 1.09, 1.18) for women with less than a high school education and 92% lower (aOR 0.08, 95% CI: 0.08, 0.09) for women with a bachelor’s degree or higher, compared to women with a high school diploma. Conclusions Despite the high prevalence of high intensity smoking before and during pregnancy, future intervention strategies need to focus on the proportion of low intensity quitters and reducers, who are ready to stop smoking. Continual monitoring of trends in smoking intensity patterns is necessary, including neonatal outcomes over time.